In pursuit of just sustainability - Culwick Fatti, Christina; Cohen, Brett; Jennings, Gail; Kane, Lisa; Rubin, Margot; Tyler, Emily (Gauteng City-Region Observatory, 2021)
This volume is the product of a research collective that brought together researchers from different backgrounds to explore just sustainability in Gauteng. This research collective, which was initiated by the volume’s editor emerged out of a desire to explore from a range of perspectives those instances where social justice and environmental sustainability are not neatly aligned. The aim of such an exploration is to refine how just sustainability is conceptualised and put into practice.
Keywords: justice, sustainability, infrastructure